The Compliance Evolution of The Corporate Governance Codes in Emerging European Countries – A Content Analysis Perspective - Pompei Mititean (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - Does the corporate governance codes from 18 Emerging European countries respect the European Commission recommendations? Motivation - The corporate governance is a wildly debated topic in the literature but only few studies are addressed to the level of compliance between the corporate governance and the European Commission recommendations, especially in emerging countries. Idea - The objective of this study is to analyse the corporate governance codes form eighteen Emerging European Countries and examine if these countries comply with the recommendations of European Commission regarding corporate governance by using the content analysis technique. The main research proposition is to identify how many out of the 32 recommendations included in this analysis are fulfilled by the corporate governance codes from the Emerging European Countries and how these developed during time. Data - Data sample consists of 18 corporate governance codes from Emerging European Countries, which are examined in the context of the recommendations of European Commission COM-284, and the next years updates from 2004 (2004/913/EC), 2005 (2005/162/EC) and 2009 (2009/384 and 385/EC), divided into five group, covering 32 recommendations. Tools - The latest versions of corporate governance codes from each country, from 2004-2020, were downloaded, collecting the data manually from each corporate governance code using the content analysis technique. Findings - The results illustrate that Slovenia and Czech Republic are the countries with the highest compliance degree, while Poland and Estonia are the countries with the least fulfilled recommendations Contribution - This paper provides a general overview regarding the level of compliance of the corporate governance codes and European Commission recommendations, thus being a starting point for researchers who will further study this subject. Secondly, we have contribute to the limited studies that analysed the evolution of corporate governance codes following the best practices for the companies issued by European Commission.
Keywords: M41; G34; 650; corporate governance; corporate governance codes; Emerging European Countries